Saturation of biological diversity and human activity - Latawiec, Michał (Studia Ecologiae et Bioethicae, 2014)
Human beings constantly interfere with nature by means of their activity. Their role in shaping the current natural world is indisputable. The problem of saturation and unsaturation in nature conservation relates to the degree of genetic diversity, flora and fauna species and ecosystems, which are managed by humans. This paper makes an attempt at answering the question as to whether one can speak of saturation in terms of biological diversity. For this purpose, the issues related to attempts at de#ning biological diversity are described. As a result, the human impact on the surrounding natural environment is discussed. To illustrate the above issues, two cases of human interference in the natural environment, characterized by rich and poor biodiversity, are discussed.